Entre cerros : tejiendo comunidades (2020)
Entre Cerros is an architectural project that responds to the diversity on the AOE and the deficit of public space and residential units. In addition, his objective is to provide an integral architecture by the mix of uses and types of residential units that allows the union of those different communities in the zone of Los Martires, Bogotá. The seed that pretends to be Entre Cerros will be reflected in different ways: The value of the education and the early childhood. The development of public space of quality for a zone that has the lowest levels of effective public space per habitant in the city. Finally, Entre Cerros is a project that's looking for bring new communities and families to the AOE, taking into account big qualities like the ubication, low density and the visual connection whit the Cerros Orientales. The residential units are built by the concept of flexible homes, the understand of residential unit starts from a space that evolves and changes on the time, adapting to the different needs of the habitants and the Nucleos familiares. Taking into account the diversity of families on the AOE, that is a aggregate value of the project. The social home, starts from a structural module of 8.40 mts x 4.80 mts. This module allows 3 habitable spaces, all of them with natural illumination and ventilation, in addition with a zona of 1.20 mts of circulation or wet zones like kitchen or bathrooms. Each module has 40 m2 that is ready for different kinds of families and types of living found in the sector. Those residential units can connect with others modules, allowing productive homes, duplex, and side to side apartments. With a occupation index of 50%, and the rest for public space of quality and a density of 4 ? 5 floors, Entre Cerros is a integral project that respect and dialogue with his environment.